2021
DOI: 10.1186/s12877-021-02557-4
|View full text |Cite
|
Sign up to set email alerts
|

Support system diversity among family caregivers of stroke survivors: a qualitative study exploring Asian perspectives

Abstract: Background Caregiving is a global phenomenon which is bound to increase in tandem with the aging population worldwide. Stroke is a condition common in older people that requires complex caregiving necessitating provision of adequate support to the caregivers. Past literature consists of limited accounts of types and organization of support arrangements needed by different caregivers. We aimed to describe the support system of caregivers of stroke survivors in Singapore, highlighting differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Family members are the most important caregivers of stroke patients (Tyagi et al, 2021). In our study, we counted the number 10.3389/fnagi.2024.1366380 of caregiver roles in three categories: spouse, adult children, and other relatives.…”
Section: Caregivermentioning
confidence: 99%
See 1 more Smart Citation
“…Family members are the most important caregivers of stroke patients (Tyagi et al, 2021). In our study, we counted the number 10.3389/fnagi.2024.1366380 of caregiver roles in three categories: spouse, adult children, and other relatives.…”
Section: Caregivermentioning
confidence: 99%
“…The reasons for this may be two fold. On the one hand, for patients with severe stroke and concurrent mobility impairment, cognitive impairment and other neurological deficits, being an adult child shows a more active role in monitoring changes in the patient's condition, improving communication with the health care team and helping the patient in making medical decisions during the early stages of the illness (van Ryn et al, 2011;Shin et al, 2013;Isenberg et al, 2018;Fenton et al, 2022).A study in Singapore noted that by adult children taking turns in care, pooling resources, and distributive support (determining which part of care each person is competent in), patients avoid to some extent the influence brought about by medical decision-making activities and become less dependent (Tyagi et al, 2021); on the other hand, it has been noted that the cultural context influences the tendency for children to care for their parents, which has an impact on the children's own lives and work. In this regard, parents feel guilty and try to reduce their needs to ease the burden of their children (Liu et al, 2020b;Liu, 2021;Nursiswati et al, 2022), resulting in an apparent "low dependency".…”
Section: Caregivermentioning
confidence: 99%
“…Caregiving capability, a crucial indicator for satisfying patients' psychosocial needs (Kosberg & Cairl, 1986), seeking social support, and performing caregiving tasks, plays a significant role in predicting BF. Research has indicated that caregivers with high caregiving capability also have a clear advantage in handling their own and patients' emotional coping styles (Tyagi et al, 2021). The higher the caregiver's capability, the more conducive it is to convey positive treatment beliefs to patients during the caregiving process and enhance positive experiences.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ] With current medical advancements, family caregivers are expected to provide continuous care to stroke-afflicted family members who have exhibited complex stroke symptoms, increased functional dependency, cognitive impairments, and behavioral problems for years following the onset of the condition. [ 3 , 4 ] Caregiving is a public health issue [ 5 ] as family caregivers are the bedrock of long-term home care given their provision of unpaid care (economically valued at an estimated US$ 470 billion) to disabled family members. [ 6 , 7 ] However, studies suggest that caregiving-associated stressors may be detrimental to the psychosocial well-being of caregivers, thereby influencing the perceived health of caregivers.…”
Section: Introductionmentioning
confidence: 99%